Nurses' Performance and Perceived Barriers Regarding Pressure Ulcers' Prevention for Critically Ill Patients at Baghdad Teaching Hospitals - Haider Mohammed Majeed; Ahmed Fleih Hassan; Ali Hussein Alek Al-Ganmi (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives Pressure ulcers are one of the most common hospital-acquired major conditions that occur in patients with mobility limitations and result in endangering patient safety, prolonging hospital stay, disability, and death. This study aims to examine the level of nurses' practices and perceived barriers for preventing pressure ulcers among critically ill patients. Materials and Methods A cross-sectional survey was conducted among nurses working in critical care units (CCUs) at a tertiary teaching hospital in Baghdad, Iraq, between January 2024 and June 2024. A non-probability purposive sampling technique was carried out involving 100 nurses with at least 6 months of experience in critical care units. The data were collected using a structured interviewing questionnaire to assess nurses' sociodemographic characteristics and an observational checklist to assess nurses' practice regarding pressure ulcer prevention. The questionnaire also assessed nurses' perceived barriers for pressure ulcer prevention. Data analysis was performed using SPSS version 26, applying descriptive and inferential statistics, including the Chi-square test, with a significance level set at P < 0.05. Results This study found that 54% of nurses were males with a mean age of 28.21 within years, ranging from 18 to 54 years. Most nurses held bachelor's degree in nursing (65%), 43% of them had <5 years of experience working in CCUs, and 45% and there was moderately of them had 1-5 years of experience in the nursing profession. Fifty-six percent of nurses were single and the same percentage received training about pressure ulcer preventions. Nurses in the critical care units were found to have a satisfactory level of practices withing (61%) of them and have moderately high levels (M±SD: 0.66 ± 0.45) of perceived barriers towards pressure ulcer prevention. A significant relationship was found between nurses' practices and their perceived barriers for preventing pressure ulcers (P < 0.05). Conclusions This study concluded that approximately two-thirds of nurses have adequate level of nursing practice to prevent pressure ulcer. Furthermore, the study identified several barriers perceived to affect patients' quality of care and prevention of pressure ulcers. Hence, this study suggests that the barriers for promoting nursing practice toward the prevention of pressure ulcers need to be contained and guaranteed in CCUs.